Sinkronus vs asinkronus pembelajaran sejarah daring: Studi korelasional di SMA Kota Bandung (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
According to preliminary observation, the most commonly used learning platforms for high school history teachers in Bandung are Google Classroom which accommodates asynchronous learning, and Zoom Cloud Meeting, which provides synchronous learning. Therefore, it is necessary to research its use on the effectiveness of student learning in history learning. This research aims to obtain information about the correlation between using the Zoom Cloud Meeting and Zoom Cloud Meeting with students’ effectiveness in History learning. The method used in this research is a correlation. The research populations were students in Bandung Senior High School, with research samples of 387 students. The instrument used was a questionnaire designed based on Davis’s Theory Acceptance Model (TAM) and indicators of learning effectiveness by Slavin. The results of this research on the correlation between synchronous learning through Zoom Cloud Meeting and Zoom Cloud Meeting with the effectiveness of student learning are as follows: 1) There is a positive, significant, and moderate correlation between asynchronous learning through Google Classroom with the effectiveness of student learning, 2) There is positive, significant, and strong correlation between synchronous learning through Zoom Cloud Meeting and the effectiveness of student learning, 3) There are a positive, significant, and solid correlation between the combination of asynchronous and synchronous learning through Google Classroom and Zoom Cloud Meeting with the effectiveness of student learning.
Keywords: Google Classroom; Learning Effectiveness; Zoom Cloud Meeting